NEUROINCLUSION AT WORK: TRANSLATING NEUROSCIENCE INTO PRACTICAL HR POLICIES FOR COGNITIVE DIVERSITY - Edo Saputra; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The increasing recognition of neurodiversity in the workplace has highlighted the need for more inclusive and adaptive human resource management practices. This study explores the concept of neuroinclusion and examines how insights from neuroscience can be translated into practical HR policies that support cognitive diversity. Drawing on a qualitative and conceptual research design, the study integrates literature from neuroscience, organizational behavior, and HR management to develop a framework for neuroinclusive workplaces. The findings indicate that traditional HR systems often fail to accommodate diverse cognitive profiles, creating barriers for neurodivergent individuals. By incorporating neuroscience-informed approaches into recruitment, performance management, and workplace design, organizations can create more inclusive environments that enhance employee engagement and performance. The study also highlights the importance of governance mechanisms, such as the algorithmic auditor, in ensuring ethical and transparent use of AI in HR systems. The proposed framework emphasizes flexibility, individualized support, and continuous learning as key components of neuroinclusion. This research contributes to both theory and practice by offering actionable insights for organizations seeking to integrate cognitive diversity into their strategies. It concludes that neuroinclusion is essential for fostering innovation, equity, and long-term organizational success.